2014
DOI: 10.18311/mvpjms/2014/v1/i1/831
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Role of Zinc Supplementation on Growth of Low Birth Weight Infants

Abstract: This was a randomized controlled trial undertaken to study the role of zinc supplementation on growth of low birth weight infants (b.wt≤2500 gm). Out of 120 LBW infants, 23 were excluded due to loss of follow up. The remaining 97 LBW eligible neonates were randomized in to 2 group (zinc & control group), zinc group were given zinc supplementation at a dose of 2 mg/kg/day for 8 weeks from enrollment. They were then followed up every 4 weeks up to 8 weeks. At each visit, detail anthropometry including e weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…[14] who found that zinc supplementation to preterm babies for 4 weeks resulted in improved weight gain and linear growth and in contrary to us head circumference also showd improved growth. Also this is in agreement with Ravindra Sonawane, et al [15] who shows in their study that zinc supplementation at 2 mg/kg/day for 8 weeks in LBW infants have significantly higher weight gain, length, linear growth velocity and head cicumference at 8 weeks ,but in our study head circumference showed no improvement in relation to control group .…”
Section: Results:-supporting
confidence: 93%
“…[14] who found that zinc supplementation to preterm babies for 4 weeks resulted in improved weight gain and linear growth and in contrary to us head circumference also showd improved growth. Also this is in agreement with Ravindra Sonawane, et al [15] who shows in their study that zinc supplementation at 2 mg/kg/day for 8 weeks in LBW infants have significantly higher weight gain, length, linear growth velocity and head cicumference at 8 weeks ,but in our study head circumference showed no improvement in relation to control group .…”
Section: Results:-supporting
confidence: 93%